1996
DOI: 10.2307/4002877
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Fire Effects within Xeric Sage Grouse Brood Habitat

Abstract: We investigated the short-term iniluence of tire on xeric sage grouse (Centrocercus urophasianus) brood habitat in southeastern Idaho from 1990-92. A prescribed fire in 1989 removed Wyoming big sagebrush (Artemisia tridentata wyomingensis Nutt.)/threetip sagebrush (A. trijlartzb Rydb.) canopy cover from approximately 57% of a 5,800-ha area, potentially intluencing brood-rearing habitat. Although the fire created a mosaic of sagebrush areas interspersed with open areas having abundant grasses and forbs, the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 19 publications
7
62
1
Order By: Relevance
“…found that prescribed fire in Oregon decreased sagebrush cover, but increased total forb cover and diversity, hypothesizing that prescribed fire may increase forbs in montane sagebrush habitats used for brood-rearing. However, Fischer et al (1996a) found that forb cover was similar in burned and unburned areas of Wyoming big sagebrush in Idaho, but the abundance of hymenoptera was lower in burned habitats. Sage-grouse abundance was not different between burned and unburned areas, and the authors indicated that fire did not enhance sage-grouse brood-rearing habitats (Fischer et al 1996a).…”
Section: Sage-grouse Habitat Characteristics 4 -16mentioning
confidence: 88%
See 1 more Smart Citation
“…found that prescribed fire in Oregon decreased sagebrush cover, but increased total forb cover and diversity, hypothesizing that prescribed fire may increase forbs in montane sagebrush habitats used for brood-rearing. However, Fischer et al (1996a) found that forb cover was similar in burned and unburned areas of Wyoming big sagebrush in Idaho, but the abundance of hymenoptera was lower in burned habitats. Sage-grouse abundance was not different between burned and unburned areas, and the authors indicated that fire did not enhance sage-grouse brood-rearing habitats (Fischer et al 1996a).…”
Section: Sage-grouse Habitat Characteristics 4 -16mentioning
confidence: 88%
“…However, Fischer et al (1996a) found that forb cover was similar in burned and unburned areas of Wyoming big sagebrush in Idaho, but the abundance of hymenoptera was lower in burned habitats. Sage-grouse abundance was not different between burned and unburned areas, and the authors indicated that fire did not enhance sage-grouse brood-rearing habitats (Fischer et al 1996a). found that sage-grouse were willing to used areas impacted by both prescribed burns and wildfires in Wyoming, but that the area's suitability appeared to be related to age of the burn and the availability of alternate shrubs.…”
Section: Sage-grouse Habitat Characteristics 4 -16mentioning
confidence: 88%
“…3). This effect is mediated by fundamental changes to the vegetation community coincident with establishment of exotic plants (Fischer et al 1996, Wambolt et al 2001, Beck et al 2009, Miller et al 2011), and appears to affect recruitment more strongly than adult survival. The historic importance of wildfire in maintaining the sagebrush ecosystem is debated (Baker 2006, Norton et al 2007, Baker 2011), but it is generally agreed that the introduction of cheatgrass has fundamentally changed the way ecologists and managers must view the contemporary role of fire in sagebrush communities (Baker 2011).…”
Section: Discussionmentioning
confidence: 99%
“…From this collection of research, much has been learned about the vegetative habitat requirements for sage grouse at various life stages. Great attention has been given to sage grouse nesting habitat (Klebenow 1969, Peterson 1980, Wakkinen 1990, Gregg 1991, Connelly et al 1991, Wakkinen et al 1992, Fischer et al 1993, Webb 1993, Musil et al 1994, Nelle 1998, Sveum et al 1998, and brood rearing habitat (Gray 1967, Wallestad 1971, Klott and Lindzey 1990, Fischer et al 1996, Nelle 1998, Sveum et al 1998). Less attention has been given to adult spring/summer habitat requirements (Martin 1970, Wallestad and Schladweiller 1974, Braun et al 1977, Schoenberg 1982, Hulet 1983, Martin 1990, Musil et al 1994, Apa 1998 (Connelly et al 1991) has measured the area within the canopy of sagebrush.…”
Section: Introductionmentioning
confidence: 99%